L16 Orthogonal Design Synthesis of NASICON-type Li1.4Al0.4Ti1.6(PO4)3 Solid Electrolyte by Pechini Method for Process Optimization - M. R. Ghaani; P. Marashi (Iranian Journal of Materials Science and Engineering, 2018)
Na super ionic conductive (NASICON) materials are ceramics with three-dimensional scaffolds. In this study, Li1.4Al0.4Ti1.6(PO4)3 with NASICON structure was synthesized by Pechini method. As a result, a sample having a total conduction of 1.18×10-3 S cm-1 was attained. In addition, various parameters were studied to obtain high value of conductivity, by optimizing the process. The optimization was made using L16 Taguchi based orthogonal array, followed by ANOM, ANOVA and stepwise regression. As a result, the optimum synthesis parameters can be obtained, while pH of the solution was adjusted to 7. The ratio between the concentration of citric acid to metal ions and ethylene glycol concentration stuck to 1 and 2.5, respectively. The best heat treatment can be carried out with a combination of pyrolysis at 600 ºC and sintering at 1000 ºC.